2009
DOI: 10.1104/pp.109.142158
|View full text |Cite
|
Sign up to set email alerts
|

The ArabidopsisRESURRECTION1Gene Regulates a Novel Antagonistic Interaction in Plant Defense to Biotrophs and Necrotrophs

Abstract: We report a role for the Arabidopsis (Arabidopsis thaliana) RESURRECTION1 (RST1) gene in plant defense. The rst1 mutant exhibits enhanced susceptibility to the biotrophic fungal pathogen Erysiphe cichoracearum but enhanced resistance to the necrotrophic fungal pathogens Botrytis cinerea and Alternaria brassicicola. RST1 encodes a novel protein that localizes to the plasma membrane and is predicted to contain 11 transmembrane domains. Disease responses in rst1 correlate with higher levels of jasmonic acid (JA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 97 publications
(118 reference statements)
1
48
1
Order By: Relevance
“…Thus, we examined the expression levels of several defense-related genes by RT-PCR. Pathogenesisrelated (PR) genes PR1 and PR2 are SA pathway defense genes (Mang et al, 2009). Phytoalexin deficient 4 (PAD4) and Enhanced Disease Resistance 1 (EDS1) act upstream from SA biosynthesis but are also induced by SA (Rustérucci et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we examined the expression levels of several defense-related genes by RT-PCR. Pathogenesisrelated (PR) genes PR1 and PR2 are SA pathway defense genes (Mang et al, 2009). Phytoalexin deficient 4 (PAD4) and Enhanced Disease Resistance 1 (EDS1) act upstream from SA biosynthesis but are also induced by SA (Rustérucci et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…The Arabidopsis glycosylphosphatidylinositol-anchored lipid transfer protein (ltpg1) mutant shows increased susceptibility to A. brassicicola attributed to changes in cuticle composition and structure further confi rming the link between altered cuticles and resistance to necrotrophic fungi (Lee et al, 2009b). In the case of rst1, increased resistance to B. cinerea and A. brassicicola is accompanied with susceptibility to the biotrophic fungal pathogen Erysiphe cichoracearum (Mang et al, 2009). Mutation in RST1, encoding a transmembrane protein of unknown biochemical function, leads to increased cutin monomers on the leaf surface without altered permeability.…”
Section: The Intriguing Roles Of the Plant Cell Wall And Cuticle In Amentioning
confidence: 99%
“…This, coupled with an increased cuticle permeability that allows easier diffusion of defense signals to the infection site, is hypothesized to promote resistance (Bessire et al, 2007b; Chassot et al, 2007). However, mutant comparisons indicate that the degree of permeability does not directly correlate with level of resistance and is unaffected in rst1 (Mang et al, 2009;Voisin et al, 2009). It was also suggested that mutant plants compensate the functional disorder of the cuticle by reinforcing their defenses thereby enhancing resistance independent of the changes in actual cuticle composition (Voisin et al, 2009).…”
Section: The Intriguing Roles Of the Plant Cell Wall And Cuticle In Amentioning
confidence: 99%
See 2 more Smart Citations